The Development of Thermoresponsive Multifunctional Chitosan Films Suitable for Food Packaging - SARIER, NİHAL; ELOĞLU, ANIL; Önder, Emel (MDPI, 2025)
We developed bio-based chitosan-gelatin films, CHG-LO films, incorporating lavender essential oil (15-26 wt% LO) and oleic acid (33-47 wt% OA) with smooth surfaces and thicknesses of 0.42-0.99 mm. For their manufacture, the nanoemulsions were prepared to possess uniform dispersion and colloidal stability with average droplet sizes of 475-854 nm, polydispersity indices (PDI) of 0.095-0.235, and zeta potentials of 23.7-56.9 mV at 40 degrees C, where OA served as surfactant and phase change material. The opacities of the CHG-LO films increased by 1.8 to 5.5 times compared to the control group, and their UV-visible light-blocking properties improved. These films demonstrated cyclic thermal buffering character, with heat storage capacities ranging from 14.0 to 36.0 Jg-1 between -26 degrees C and 20 degrees C compatible with that of OA. Additionally, they showed reduced water vapor transmission rates and swelling degrees in acidic and neutral environments. The total phenolic contents of the CHG-LO films increased 1.5-4.2 times compared to the control associated with the presence of LO phenolic groups in the structure. DPPH (2,2-diphenyl-1 picrylhydrazyl) and ABTS (2,2 '-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)) scavenging activity test results show that the antioxidant properties of these films improved with increasing LO-OA content up to 2.2 and 1.3 times the control, respectively, and also showed antimicrobial properties. The multifunctional CHG-LO films of this study are promising candidates for temperature-sensitive active packaging in food as well as in pharmaceutical and cosmetic industries.
Keywords: AFM; Chitosan; Contact Angle; DSC; Gelatin; Lavender Oil; Oleic Acid; PCM; XRD